Identification of the shark species Rhizoprionodon lalandii and R-porosus (Elasmobranchii, Carcharhinidae) by multiplex PCR and PCR-RFLP techniques - Mendonca, F. F. [UNESP]; Hashimoto, D. T. [UNESP]; Porto-Foresti, Fábio [UNESP]; Oliveira, C. [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Foresti, Fausto [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Rhizoprionodon lalandii and R. porosus are widely distributed along the Atlantic coast of the Americas, living close to coastal areas and therefore frequently captured by seaboard fisheries. However, morphological identification of species in this genus is very difficult, especially when sharks have their heads and fins removed, making information about fishing, trading, and the evaluation of fishery effects on species conservation very difficult. This study's main objective is to develop molecular tools to identify these species using multiplex polymerase chain reaction (PCR) and PCR-restriction fragment length polymorphism techniques. Both techniques result in good low-cost markers and may be very useful in future studies about the exploitation of these species.
Keywords: conservation; forensic genetics; identification of commercial species; Rhizoprionodon